Taxonomic significance of microspores in some selected species of the family Selaginellaceae from Arunachal Pradesh, India. (3rd April 2023) - Aran, Khencha; Giri, Priti; Roy, Himu; Uniyal, Prem Lal
Abstract: The microspores morphology of 18 species of Selaginellaceae found in Arunachal Pradesh, North East India, is studied using light microscopy and electron microscopy. Of the 18 taxa examined here, the study of five taxa is attempted for the first time using an electron microscope. The species studied exhibit variation in size, shape, color and ornamentation of the microscpores. The equatorial diameter ranges from 11 to 57 µm. The tetrad form of the microscpores is recorded in four species. The variations in the microscpores ornamentation within the species of the family are useful in identification, classification and taxonomic distinction of the species. An identification key is provided for the species under study. This research is beneficial for the enumeration of basic information of microspores of the family and for the precise identification of Selaginella species. Statistical analysis of the distal and proximal surface ornamentation of the microspores is also provided.